A lidar-based openness index to aid conservation planning for grassland wildlife - Michael C. Allen; Thomas Almendinger; Charles T. Barreca; Julie L. Lockwood (Resilience Alliance, 2022)
Visual openness is a key element in habitat selection for many animals of grasslands and other open habitats, especially birds. Obstructions to visual openness in the form of human infrastructure or inopportune woody vegetation growth can lead to habitat avoidance, and thus pose conservation challenges. Here we introduce a remotely sensed, lidar-based index of visual openness. Like previous indices of visual openness, ours is based on the vertical angle to the horizon; however, its calculation from remotely sensed data allows it to be easily mapped across the landscape. We illustrate its potential usage by calculating the index multiple ways within two large fields in central New Jersey, USA, and evaluating the effects of openness on habitat use by a grassland bird, the Grasshopper Sparrow (Ammodramus savannarum), within an occupancy modeling framework. We used the best performing model and digitally edited openness maps to project population responses under five hypothetical management scenarios of increased habitat openness. Occupancy modeling revealed that a version of the index calculated based on the maximum angle to the horizon best explained Grasshopper Sparrow occupancy patterns. Models also revealed that Grasshopper Sparrows showed a negative response to openness reductions caused by both powerlines and trees. Predictions based on the increased openness scenarios indicated that removal of tree lines and powerlines could increase patch-level occupancy of the sparrows in the affected fields by up to 15% and 9%, respectively. Where adequate data exist, this index has the potential to facilitate the study of openness-habitat use relationships in a variety of open-dwelling fauna and in a variety of habitats, from tundra to marshes to grasslands. Notably, it has promising potential for use in modeling habitat suitability and projecting potential impacts in response to anthropogenic changes in visual openness, such as wind farms, power infrastructure, or vegetation management.